Monitoring the physical processes driving the mass loss of Tapado Glacier, Dry Andes of Chile - Álvaro Ayala; Benjamin Robson; Gonzalo Navarro; Shelley MacDonell; Christophe Kinnard; Sebastián Vivero; Daniel Thomas; Felipe Moreno; Eduardo Yáñez; Nicole Schaffer; Alexis Segovia; Michał Pętlicki; et al. (Journal of Glaciology)
We summarise 15 years of field and remote monitoring of Tapado Glacier in north-central Chile (30° S). Observations include meteorological records, direct mass balance measurements, uncrewed aerial vehicle surveys and tri-stereo satellite imagery for deriving high-resolution elevation changes. Frequent droughts and a significant warming trend of 0.29°C decade−1 since 1974 have caused a decrease in glacier surface albedo and an accelerated loss of glacier area and mass, particularly since the onset of the Chilean Megadrought in 2010, associated here with a 43% winter precipitation deficit. Geodetic estimates indicate increasingly more negative mass balance, varying from slightly negative before 2000 to −0.18 ± 0.35 m w.e. a−1 in 2000–12, −0.44 ± 0.11 m w.e. a−1 in 2012–20 and −0.75 ± 0.12 m w.e. a−1 after 2020. Glacier mass loss is associated with several morphological changes, such as increased penitente height, a larger total surface area of ice cliffs and supraglacial ponds over the debris-covered section and more frequent falls of snow and ice from marginal ice surrounding a steep area of exposed bedrock. Tapado Glacier exemplifies how glacier mass loss is driven by various processes, requiring multiple monitoring techniques, and highlights the accelerated changes of the Andes cryosphere.